2009
DOI: 10.1038/ajg.2009.361
|View full text |Cite
|
Sign up to set email alerts
|

Light and Moderate Alcohol Consumption Significantly Reduces the Prevalence of Fatty Liver in the Japanese Male Population

Abstract: The prevalence of FL was significantly and independently decreased by light and moderate alcohol consumption in men of an asymptomatic Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 45 publications
5
94
2
Order By: Relevance
“…The National Institute on Alcohol Abuse and Alcoholism (NIAAA) defines heavy or at-risk drinking as more than 4 drinks on any day or more than 14 drinks per week in men or more than 3 drinks on any day or 7 drinks per week in women. 146 Several recent cross-sectional studies [147][148][149][150][151][152][153] suggest a beneficial effect of light alcohol consumption (on average less than one drink per day) on the presence (defined either biochemically or by imaging) and severity of NAFLD. There are no studies reporting the effect of ongoing alcohol consumption on disease severity or natural history of NAFLD or NASH.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…The National Institute on Alcohol Abuse and Alcoholism (NIAAA) defines heavy or at-risk drinking as more than 4 drinks on any day or more than 14 drinks per week in men or more than 3 drinks on any day or 7 drinks per week in women. 146 Several recent cross-sectional studies [147][148][149][150][151][152][153] suggest a beneficial effect of light alcohol consumption (on average less than one drink per day) on the presence (defined either biochemically or by imaging) and severity of NAFLD. There are no studies reporting the effect of ongoing alcohol consumption on disease severity or natural history of NAFLD or NASH.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Interestingly, in contrast, several studies have shown a beneficial effect of moderate alcohol intake. Moderate alcohol use was shown to be protective against insulin resistance in morbidly obese individuals [73] , was associated with decreased prevalence of fatty liver in asymptomatic individuals [99] , and with decreased prevalence of steatohepatitis in NAFLD patients [100] . The pathologist is not able to recognize the relative contributions of NAFLD or ALD to the liver injury in a biopsy with steatohepatitis.…”
Section: Histological Findings Of Nafld/ Nash In Concurrence With Othmentioning
confidence: 99%
“…044 and 0 . 008, respectively) (89) . In another study, also in Japanese population, the major risk factors for FL in Japanese men were factors related to adiposity, while consistent alcohol consumption (> 21 d/month) was inversely associated with the prevalence of FL (90) .…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%